Relevance of Recurring Esthetic Dental (RED) proportion and golden proportion among patients attending a tertiary care center at Kochi, Kerala - Gurmehr Baghiana; Deepa Peter; V. Manju; Anna Serene Babu; Vinod Krishnan (Elsevier, 2022)
Background: Smile plays an essential part in facial esthetics. There have been some mathematical and geometric theories regarding smile designing in literature. The purpose of the study was to assess RED proportion and golden proportion among patients attending a tertiary care centre at Kochi, Kerala. Methods: Standardised frontal images of 106 subjects, 50 male and 56 females, were captured in the age bracket of 18-25 years. Pictures of the patients were obtained using a DSLR camera (CANON EOS-60D) and then digitally analysed. Measurements of each maxillary anterior tooth was recorded and then the theories of RED and golden proportion were employed and the figures recorded were statistically analysed. Results: The RED proportion was observed to be inconsistent, while progressing distally, Golden proportion was observed to be in 6-29% of the existing subject population. Conclusion: Within the limited sample size of the study, RED (Recurring Esthetic Dental) proportion and golden proportion failed to exist in Keralites.